If α = 7 2 π , find the value of tan α tan 2 α + tan 2 α tan 4 α + tan 4 α tan α .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There is a very neat way to do this problem almost mentally. (If you are comfortable with evaluating trig products in your head.)
Let's consider ( c i s x ) 7 = c i s 7 x
Expand the left side, we have c i s 7 x = ( c o s 7 x − 2 1 c o s 5 x s i n 2 x + 3 5 c o s 3 x s i n 4 x − 7 c o s x s i n 6 x ) + i ( 7 c o s 6 x s i n x − 3 5 c o s 4 x s i n 3 x + 2 1 c o s 2 x s i n 5 x − s i n 7 x )
Compare the real and imaginary parts of both side, we have c o s 7 x = c o s 7 x − 2 1 c o s 5 x s i n 2 x + 3 5 c o s 3 x s i n 4 x − 7 c o s x s i n 6 x s i n 7 x = 7 c o s 6 x s i n x − 3 5 c o s 4 x s i n 3 x + 2 1 c o s 2 x s i n 5 x − s i n 7 x
Therefore, t a n 7 x = c o s 7 x s i n 7 x = c o s 7 x − 2 1 c o s 5 x s i n 2 x + 3 5 c o s 3 x s i n 4 x − 7 c o s x s i n 6 x 7 c o s 6 x s i n x − 3 5 c o s 4 x s i n 3 x + 2 1 c o s 2 x s i n 5 x − s i n 7 x
Divide both top and bottom by c o s 7 x : t a n 7 x = 1 − 2 1 t a n 2 x + 3 5 t a n 4 x − 7 t a n 6 x 7 t a n x − 3 5 t a n 3 x + 2 1 t a n 5 x − t a n 7 x
Set t a n 7 x = 0 , we have x = 7 k π , k = 0 , 1 , 2 , . . . , 6
Therefore the equation 7 t a n x − 3 5 t a n 3 x + 2 1 t a n 5 x − t a n 7 x = 0 has those 6 roots also, plus the one x = 0
Assume x = 0 , divide the equation both side by − t a n x , we have t a n 6 x − 2 1 t a n 4 x + 3 5 t a n 2 x − 7 = 0
Thus, the equation x 6 − 2 1 x 4 + 3 5 x 2 − 7 = 0 has roots t a n 7 π , t a n 7 2 π , . . . , t a n 7 6 π
Notice that x 6 − 2 1 x 4 + 3 5 x 2 − 7 = ( x 3 + 7 x 2 − 7 x + 7 ) ( x 3 − 7 x 2 − 7 x − 7 )
So 3 of the roots go to the first factor and the last 3 remaining roots go for the second factor.
Looking at the sign of the 2 factors, it is quite certain that t a n 7 π and t a n 7 2 π are for the first factor (since that are not so large), and t a n 7 5 π and t a n 7 6 π are for the second factor (since they are negative)
Applying the famous formula t a n 7 π t a n 7 2 π t a n 7 3 π = 7 , t a n 7 3 π is not for the first factor (otherwise t a n 7 π t a n 7 2 π t a n 7 3 π = − 7 ), so it is for the second factor, and t a n 7 4 π is for the first factor
(Thus, this observation is correct)
The first factor x 3 + 7 x 2 − 7 x + 7 has root t a n 7 π , t a n 7 2 π , t a n 7 4 π . Therefore t a n 7 π t a n 7 2 π + t a n 7 2 π t a n 7 4 π + t a n 7 4 π t a n 7 π = − 7
Applying t a n ( π + y ) = t a n y , we can see t a n 7 π = t a n 7 8 π . So finally t a n 7 2 π t a n 7 4 π + t a n 7 4 π t a n 7 8 π + t a n 7 8 π t a n 7 2 π = − 7
Finally Note To lead to the final answer, this is the most convenient factorization, others can have problem with the sign or even lead to dead end.
Problem Loading...
Note Loading...
Set Loading...
Techniques used:
Since tan 7 8 π = tan 7 π , the expession is equivalent to tan 7 π tan 7 2 π + tan 7 2 π tan 7 4 π + tan 7 4 π tan 7 π
Consider tan 7 π tan 7 2 π , tan 7 π tan 7 2 π = cos 7 π cos 7 2 π sin 7 π sin 7 2 π = 2 cos 7 π cos 7 2 π cos 7 4 π ( cos 7 π − cos 7 3 π ) cos 7 4 π = 2 cos 7 π cos 7 2 π cos 7 4 π cos 7 4 π cos 7 π − cos 7 4 π cos 7 3 π = 4 cos 7 π cos 7 2 π cos 7 4 π ( cos 7 5 π + cos 7 3 π ) − ( cos π + cos 7 π )
Similarly: tan 7 2 π tan 7 4 π = cos 7 2 π cos 7 4 π sin 7 2 π sin 7 4 π = 2 cos 7 π cos 7 2 π cos 7 4 π ( cos 7 2 π − cos 7 6 π ) cos 7 π = 2 cos 7 π cos 7 2 π cos 7 4 π cos 7 π cos 7 2 π − cos 7 π cos 7 6 π = 4 cos 7 π cos 7 2 π cos 7 4 π ( cos 7 3 π + cos 7 π ) − ( cos π + cos 7 5 π ) tan 7 π tan 7 4 π = cos 7 π cos 7 4 π sin 7 π sin 7 4 π = 2 cos 7 π cos 7 2 π cos 7 4 π ( cos 7 3 π − cos 7 5 π ) cos 7 2 π = 2 cos 7 π cos 7 2 π cos 7 4 π cos 7 3 π cos 7 2 π − cos 7 5 π cos 7 2 π = 4 cos 7 π cos 7 2 π cos 7 4 π ( cos 7 5 π + cos 7 π ) − ( cos π + cos 7 3 π ) All them all up, some terms cancel, we are left with tan 7 π tan 7 2 π + tan 7 2 π tan 7 4 π + tan 7 4 π tan 7 π = 4 cos 7 π cos 7 2 π cos 7 4 π cos 7 π + cos 7 3 π + cos 7 5 π + 3 = 8 sin 7 π cos 7 π cos 7 2 π cos 7 4 π 2 ( cos 7 π + cos 7 3 π + cos 7 5 π + 3 ) sin 7 π = sin 7 8 π 2 sin 7 π cos 7 π + 2 cos 7 3 π sin 7 π + 2 cos 7 5 π sin 7 π + 6 sin 7 π = sin 7 8 π sin 7 2 π + ( sin 7 4 π − sin 7 2 π ) + ( sin 7 6 π − sin 7 4 π ) + 6 sin 7 π = sin 7 8 π sin 7 6 π + 6 sin 7 π = − sin 7 π sin 7 π + 6 sin 7 π = − sin 7 π 7 sin 7 π = − 7